Efektivitas Komik Digital dalam Meningkatkan Kesadaran Dampak Bullying Siswa Tingkat Sekolah Dasar - Oktavia Annisa Cahyaningtias; Nor Riza Maftiyana; Muhammad Ashfal Fu'adi; Eny Kusumawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Many incidents that should not occur in schools continue to take place, ranging from teasing classmates, clapping mockingly, calling friends by their parents' names, excluding certain students during group formation, not inviting them to play or go to the canteen together, to social exclusion, provocation, intimidation, bullying, and even refusing to sit at the same table with the victim. Along with technological advancements, comics have evolved from printed books into digital formats. One educational innovation that can be utilized is digital comics as a learning medium. Digital comics combine educational text and images to provide visual simulations that engage students in the learning process. This study employed the Research and Development (R&D) method, which is used to develop a particular product and evaluate its effectiveness. The purpose of this study was to determine whether digital comics could help students better understand complex concepts related to the impact of bullying on self-esteem, as well as to assess the effectiveness of digital comics as a learning medium. This was reflected in students’ positive responses to the use of digital comics in learning activities. The findings also indicated that the use of digital comics improved students’ information retention. Through the visual and narrative experiences presented in the comics, students were able to remember information more easily. This helped them better understand and internalize concepts related to bullying and self-esteem.